Legalitas Pemungutan Parkir Tepi Jalan Umum di Kota Kupang: Telaah Konstitusional terhadap Praktik Pemerintahan Daerah - Jenny Ermalinda; Chatryen M Dju Bire; Adhe Ismail Ananda; Daud Yaferson Dollu; Cyrilius Wilton Taran Lamataro (Sekolah Tinggi Ilmu Administrasi (STIA) Yappi Makassar, 2026)
This study examines the legality of on-street parking levy practices in Kupang City from a constitutional law perspective, with a primary focus on the application of the legality principle. The background of this research stems from a significant discrepancy between the legal norms established in statutory regulations and the empirical administrative practices occurring in the field. Identified issues include the collection of levies without official tickets, the lack of clarity regarding the identity and legal status of collection officers, and the inconsistent and non-transparent application of parking tariffs. This research employs a normative-empirical legal method by applying statutory, conceptual, and empirical approaches through limited field observations. The findings indicate that although the Kupang City Government formally possesses the attribution of authority to collect parking levies, the implementation frequently deviates from the established legal procedures. Such deviant practices potentially constitute ultra vires actions and violate the principle of due process of law in government administration. This study concludes that the substantive legality of parking levies in Kupang City has not been fully realized, thereby undermining legal certainty and public trust in the legitimacy of local governance. The implications of this research emphasize the imperative for comprehensive reform of the supervision system and stricter enforcement of administrative procedures to ensure the rule of law at the local level.